Modificação de quitosana com ácido hialurônico e sua blenda com colágeno para aplicação biomédica - Souza, Winicius (Universidade Federal de São Carlos, 2019)
As in other areas of application, researchers in the field of biomaterials have been looking for materials from natural sources for the installation of implantable or curative devices, in this sense, a chitosan has been much studied. In spite of the properties that favor its application, its solubilization requires the use of acetic acid, whose result, in the structure of the scaffold, can impair an interaction as the host cells. In order to minimize this problem, the present work aimed to chemistry of chitosan with hyaluronic acid (HA) and to obtain its blend with collagen. Thus, the advantage is the following chitosan (Qm) chemistry to become useful in water and, in addition, provides a scaffold for the presence of AH, a glycosaminoglycan, a major component of the skin, to engage in tissue payment processes. The chitosan and AH changes were verified through the FTIR technique, where a chemical interaction with the reactive groups of the chitosan molecules was evidenced. The solubility test demonstrated great success with the water-soluble chitosan solution. The scaffolds, obtained by the lyophilization method, are the porous morphology and depend on the concentration of Qm, with concentrations of 9% and 17% of the highest porosity. The swelling test in phosphate-saline solution (PBS) showed that the scaffold with lower concentration of Qm (9%) was the one with the highest swelling rate. In turn, the thermogravimetry assay resulted in the presence of Qm decreased the thermal stability of the collagen. Finally, the DSC assay showed the miscibility of the collagen-Qm blend since it was subjected to a single vitreous transition temperature (Tg). These data allow us to verify the feasibility of using a new blend based on properties capable of forming a porous scaffold that can be used as a cutaneous dressing.
Modification of chitosan with hyaluronic acid and its blend with collagen for biomedical application
Keywords: Modificação Química, Quitosana, Ácido Hialurônico, Blenda, Colágeno.; Chemical Modification, Chitosan, Hyaluronic Acid, Blend, Collagen.; Modificación Química, Quitosana, Àcido hialurónico, Blenda, Colágeno.; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESPECTROS ATOMICOS E INTEGRACAO DE FOTONS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESPECTROS MOLECULARES E INTERACOES DE FOTONS COM MOLECULAS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESTRUTURA ELETRONICA DE ATOMOS E MOLECULAS; TEORIA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::GRAVIMETRIA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::DETERMINACAO DE ESTRUTURA DE COMPOSTOS INORGANICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS